An analytical study to establish the role of Calendula Q as a topical wound dressing in partial-thickness burn wound - Harish Kumar Sharma; Dharm Dev; Rajpal; Chetna Deep Lamba; Piyush K Thayal; Heema (Wolters Kluwer Medknow Publications, 2022)
Objectives: The primary objective of this study was to evaluate the efficacy of Calendula officinalis in the wound healing of burn wound in comparison with standard povidone-iodine solution. Materials and Methods: A prospective randomized controlled study with 3 weeks of intervention and follow-up was conducted at the Department of Burns, Plastic and Maxillofacial Surgery, Safdarjung Hospital and VMMC, New Delhi, in collaboration with Homeopathic Treatment Centre, Safdarjung Hospital, New Delhi, from January 1, 2017, to December 31, 2018. The patients between 15 and 60 years of age reporting to the burns outpatient department with burn wounds due to thermal bums having the involvement of 5%-20% of total body surface area within 24 h of injury were randomized to either the Calendula (n = 20) or Betadine (n = 20) group. Results: There was no significant difference between the Calendula and Betadine groups, however, by day 14, 75% of cases in the Calendula group showed 80% and above epithelization as compared to 45.0% of cases in the Betadine group. Similarly, there was no significant difference between the wound discharges between the two groups but 95% had no discharge by the 14th day in the Calendula group as compared with 65% in the Betadine group. The Calendula group had a reduced incidence of wound infection when compared with Betadine. Conclusion: Therefore, Calendula dressing had a positive influence in early epithelization, better control of wound discharge, and lesser infections but these need to be evaluated on adequate sample size for a definite outcome.